WEBVTT
00:00:01.320 --> 00:00:07.760
Find the first derivative of the function 𝑦 equals four 𝑥 over nine 𝑥 squared minus seven.
00:00:08.200 --> 00:00:13.840
Now note to actually solve this problem and find our first derivative, what we’re gonna use is the quotient rule.
00:00:14.240 --> 00:00:21.720
And we can use the quotient rule because our function is actually in the form 𝑢 over 𝑣 because it’s actually has a fraction.
00:00:22.320 --> 00:00:36.240
And the quotient rule tells us that d𝑦 d𝑥 — so our first derivative — is equal to 𝑣 d𝑢 d𝑥 minus 𝑢 d𝑣 d𝑥 over 𝑣 squared.
00:00:36.600 --> 00:00:48.280
So, in practical terms, what is means is, actually, our denominator multiplied by our numerator’s derivative minus our numerator multiplied by our denominator’s derivative and this is all divided by the denominator squared.
00:00:48.880 --> 00:00:54.080
Okay, so now that we have this, let’s start to use it and actually find out what the derivative of our function is.
00:00:54.640 --> 00:00:57.680
Well, the first stage is actually to identify what our 𝑢 and 𝑣 are.
00:00:58.120 --> 00:01:07.960
So our 𝑢 is gonna be four 𝑥 and our 𝑣 is nine 𝑥 squared minus seven and that’s because they’re in fact our numerator and denominator, respectively.
00:01:08.520 --> 00:01:14.080
So next, what we’re gonna need to is actually differentiate four 𝑥 and differentiate nine 𝑥 squared minus seven.
00:01:14.440 --> 00:01:15.400
I’m gonna start with 𝑢.
00:01:15.760 --> 00:01:24.440
So we’re gonna have d𝑢 d𝑥 is equal to- well, just to remind us how we’re actually gonna differentiate.
00:01:24.880 --> 00:01:34.400
If we know that we got a function in the form 𝑎𝑥 to the power of 𝑏, then we know that our first derivative is gonna be 𝑎𝑏 𝑥 to the power of 𝑏 minus one.
00:01:35.200 --> 00:01:41.280
So what we’ve done is we multiplied the coefficient by the exponent and then we’ve actually reduced one from the exponent.
00:01:41.600 --> 00:01:46.040
So that’s why I’ve got 𝑎𝑏 𝑥 to the power of 𝑏 minus one.
00:01:46.680 --> 00:01:50.080
Okay, so let’s apply this and actually differentiate 𝑢.
00:01:50.480 --> 00:01:59.920
So if we differentiate 𝑢, we’d just gonna get four and that’s because we multiplied our coefficient which is four by the exponent which is just one so that’s four.
00:02:00.520 --> 00:02:07.520
And then, we had 𝑥 to the power of- well, one minus one is zero, so 𝑥 to the power of zero is just one.
00:02:07.960 --> 00:02:10.720
So we’re just left with four.
00:02:11.160 --> 00:02:14.200
Okay so now, let’s move on to d𝑣 d𝑥.
00:02:14.600 --> 00:02:27.000
So d𝑣 d𝑥 is just gonna give us 18𝑥 and that’s because we’ve differentiated the first term — so nine multiplied by two is 18 — and reduced the exponent by one.
00:02:27.360 --> 00:02:30.240
So we just get 𝑥 on its own.
00:02:31.120 --> 00:02:41.600
And this is just it because actually negative seven differentiates to zero because if you have an integer, they all differentiate just to zero.
00:02:42.160 --> 00:02:50.040
Okay, we now have d𝑢 d𝑥 and d𝑣 d𝑥, Let’s move on and actually apply the quotient rule.
00:02:50.480 --> 00:02:53.680
So first of all, what we’ve got is 𝑣 d𝑢 d𝑥.
00:02:54.160 --> 00:03:04.040
So it’s gonna be four multiplied by nine 𝑥 squared minus seven or run it the other way round just because it’s an easy one, we’re gonna expand the parenthesis.
00:03:04.480 --> 00:03:19.160
And this is minus four 𝑥 multiplied by 18𝑥 and this is because this is our 𝑢 d𝑣 d𝑥 and then this is all over 𝑣 squared — so nine 𝑥 squared minus seven all squared.
00:03:19.680 --> 00:03:23.680
So now, we’re gonna move on to our next stage, which is actually expanding the parentheses.
00:03:24.160 --> 00:03:41.200
So then, we have d𝑦 d𝑥 is equal to and then our first term on numerator is 36𝑥 squared because four multiplied by nine 𝑥 squared and then we have minus 28 because we have four multiplied by negative seven.
00:03:41.880 --> 00:03:46.120
And then, we finally have minus 72𝑥 squared.
00:03:46.720 --> 00:03:56.920
And this is because we have four 𝑥 multiplied by 18𝑥 which gives us 72𝑥 squared and then we have the negative sign in the middle.
00:03:57.560 --> 00:04:05.200
Okay, great, and this is all divided by our 𝑣 squared which is nine 𝑥 minus seven all squared.
00:04:05.440 --> 00:04:09.400
So then, we get on to our final stage, which is actually to simplify the numerator.
00:04:09.400 --> 00:04:18.960
And all we need to do is actually subtract 72𝑥 squared from 36𝑥 squared which is negative 36𝑥 squared.
00:04:19.240 --> 00:04:38.680
So we can now say that the first derivative with the function 𝑦 equals four 𝑥 over nine 𝑥 squared minus seven is equal to negative 36𝑥 squared minus 28 over nine 𝑥 minus seven all squared.